Zebrafish Calsyntenins mediate homophilic adhesion through their amino-terminal cadherin repeats - Ortiz-Medina, Harold (Neuroscience, 2014)
The calsyntenins are atypical members of the cadherin superfamily that have been implicated in learning in C. elegans and memory formation in humans. As members of the cadherin superfamily, they could mediate cell-cell adhesion, although their adhesive properties have not been investigated. As an initial step in characterizing the calsyntenins, we have cloned clstn1, clstn2 and clstn3 from the zebrafish and determined their expression in the developing zebrafish nervous system. The three genes each have broad, yet distinct, expression patterns in the zebrafish brain. Each of the ectodomains mediates homophilic interactions through two, aminoterminal cadherin repeats. In bead sorting assays, the calsyntenin ectodomains do not exhibit hompphilic preferences. These data support the idea that calsyntenins could either act as adhesion molecules or as diffusible, homophilic or heterophilic ligands in the vertebrate nervous system.